Tenchi warfare – modern military operations based on the “tenchijin” philosophy - Sorin TOPOR (Bulletin of "Carol I" National Defense University)
In the context of the ongoing conflict in Ukraine, the protection of material and human resources is an essential condition for regional security. The paper examines a number of trends in technological development, lessons learned from this conflict, and opportunities for applying the Japanese tenchijin philosophy to modern military operations. We propose that under the name of “Tenchi warfare” we highlight the role of advanced military technologies in military operations, with an emphasis on the exploitation of obscure spaces and knowledge, to ensure strong decision-making support in order to synchronize the rhythm of the engaged forces with the rhythm of enemy evolution. Similar to how ninja fighters approach combat, we believe such a strategy could be useful in offensive reactions in various domains, as well as for enhancing national and regional security.